Beyond Replacement Migration : Evaluating Youth Retention and Prospective Aging in Czechia, 2024–2059 - Soto Juárez, Gerardo (2025)
This thesis studies how migration and youth retention could mitigate the demographic consequences of population aging in Czechia between 2024 and 2060. Beyond only forecasting, this thesis applies the United Nations’ replacement migration framework to estimate the number of migrants required to maintain either the total population or the working-age population at its 2024 level. The model improves on the original UN approach by introducing two extensions: (1) a prospective definition of working age based on the age at which remaining life expectancy falls below 15 years (RLE15), and (2) a youth-retention counterfactual estimating the demographic effect of reducing emigration among residents aged 20–34.